2013
DOI: 10.7235/hort.2013.12148
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Genetic Diversity of Radish Germplasm through SSR Markers Derived from Chinese Cabbage

Abstract: Abstract. Since the early 1980s, the National Institute of Horticultural & Herbal Sciences has been breeding and collecting diverse radish breeds to select those samples with better horticultural characteristics, to ultimately expand and develop as good radish produce. Genetic diversity is a crucial factor in crop improvement and therefore it is very important to obtain various variations through sample collection. The collected samples were compared with one another in order to assess the level of diversity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In addition, it is a useful tool for studying the non-reference plant genome, due to its even distribution throughout the genome, as well as its high polymorphism between individuals. Therefore, many studies have reported SSR marker applications to crops for phylogenetic analysis or genetic diversity on the non-reference plant genomes (Badiane et al 2012;Bang et al 2011;Kim et al 2015;Park et al 2013;Reed and Rinehart 2009). Li et al (2009Li et al ( , 2013 identified SSR markers for C. tangshen and C. pilosula, and then successfully applied these findings to investigate the genetic diversity and population structure of these two species.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is a useful tool for studying the non-reference plant genome, due to its even distribution throughout the genome, as well as its high polymorphism between individuals. Therefore, many studies have reported SSR marker applications to crops for phylogenetic analysis or genetic diversity on the non-reference plant genomes (Badiane et al 2012;Bang et al 2011;Kim et al 2015;Park et al 2013;Reed and Rinehart 2009). Li et al (2009Li et al ( , 2013 identified SSR markers for C. tangshen and C. pilosula, and then successfully applied these findings to investigate the genetic diversity and population structure of these two species.…”
Section: Introductionmentioning
confidence: 99%
“…sequence repeat (SSR), insertion or deletion (InDel), amplified fragment length polymorphism, random amplification of polymorphic DNA, and structural variation markers (Bae et al, 2015;Lee et al, 2018;X. Li et al, 2023;S. Park et al, 2013).…”
Section: Crop Sciencementioning
confidence: 99%
“…With the development of genomic resources and tools, diverse molecular marker techniques combined with plant collections have provided opportunities to evaluate genetic diversity, construct genetic maps, and discover genes regulating important agronomic traits in different radish varieties. These molecular marker techniques include both low‐ and high‐throughput genotyping markers such as simple sequence repeat (SSR), insertion or deletion (InDel), amplified fragment length polymorphism, random amplification of polymorphic DNA, and structural variation markers (Bae et al., 2015; Lee et al., 2018; X. Li et al., 2023; S. Park et al., 2013). High‐throughput sequence‐based marker techniques including single‐nucleotide polymorphism (SNP) markers, kompetitive allele‐specific polymerase chain reaction (PCR), and restriction‐site associated sequencing have also been developed based on GWAS.…”
Section: Introductionmentioning
confidence: 99%
“…Qin et al (2014) determined that plant height, fresh leaf weight, and root length significantly affected red radish root flesh yield. However, despite these studies, little is known about the genetic diversity of red radish with red flesh because of its specific distribution, while white radish has been better characterized (Jiang et al, 2012;Park et al, 2013;Wang et al, 2015b;Zhai et al, 2013). The red pigment of radish is natural, nutritious, and multi-functional, which suggests it may have practical uses to satisfy consumer demands for natural and safe products.…”
Section: Introductionmentioning
confidence: 99%